2020
DOI: 10.3390/s20143836
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Monitoring Systems Data for Driver Distraction and Drowsiness Research

Abstract: Driver inattention is a major contributor to road crashes. The emerging of new driver monitoring systems represents an opportunity for researchers to explore new data sources to understand driver inattention, even if the technology was not developed with this purpose in mind. This study is based on retrospective data obtained from two driver monitoring systems to study distraction and drowsiness risk factors. The data includes information about the trips performed by 330 drivers and corresponding distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Xing et al [ 12 ] and Luo et al [ 19 ] both found that driver fatigue and speeding significantly impact the HAZMAT crash injury severity. One of the most prevalent causes of traffic crashes related to behavioral error is driver inattention [ 43 ]. It is associated with impaired driving performance and significant deficiencies in cognitive performance, both of which could have a negative impact on road safety.…”
Section: Resultsmentioning
confidence: 99%
“…Xing et al [ 12 ] and Luo et al [ 19 ] both found that driver fatigue and speeding significantly impact the HAZMAT crash injury severity. One of the most prevalent causes of traffic crashes related to behavioral error is driver inattention [ 43 ]. It is associated with impaired driving performance and significant deficiencies in cognitive performance, both of which could have a negative impact on road safety.…”
Section: Resultsmentioning
confidence: 99%
“…These sections also often have speed limits. The study showed that higher average speeds increased risk of inattention [43]. To shorten the travel time, the driver must take the risk of being too close and having a higher speed to complete the lane change and overtaking.…”
Section: Lane Change Across Solid Linementioning
confidence: 99%
“…An approach for the effective monitoring of drivers current state of action was proposed in [27]. In this paper, driver distraction was predicted by designing driver monitoring systems.…”
Section: Related Workmentioning
confidence: 99%